MEASUREMENT OF VIBRATION POWER FLOW IN THIN PLATE STRUCTURE WITH CROSS POWER SPECTRAL DENSITY- BASED TECHNIQUE - Nyeina, Oo Kyaw (International Journal of Psychosocial Rehabilitation, 2020)
The out of plane vibration is measured to investigate the dynamic characteristics and the power flow behavior of the plate structure. The power flow is expressed in terms of the cross power spectral density and contour map of power distribution over the plate at different natural frequencies. During measurement, the effectiveness and accuracy of the results are monitored against coherence function. The frequency response functions are also measured to generate the dynamic characteristics of the plate. The results show that the magnitudes of power flow are decreasing with respect to distance from the exciting point, and the higher natural frequency, the more spreading of vibration power over the plate. The higher vibration power flow occurs mostly near the edges of the plate. The reason of this behavior could be the boundary of the plate. These vibration power flow distribution maps provide information for the effective control of the vibration of the structure such as where the structure should be strengthened, and where the high vibration power occurs at certain frequency.